The Effect Of Application Of Aida (Attention, Interest, Desire And Action) On Telkomsel Card Purchase Decisions In Bengkulu City - Nori Dwi Apriandi; Ahmad Soleh; Tito Irwanto (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
The purpose of this study was to determine the effect of attention, interest, desire and action on Telkomsel card purchasing decisions in the city of Bengkulu.The sample in this study was 85 people from the city of Bengkulu who purchased Telkomsel cards. The sampling technique is accidental sampling technique. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing. The results of the study show that the Attention variable influences the decision to purchase Telkomsel cards in the city of Bengkulu, this is evidenced by the tcount value greater than ttable (4.233 > 1.663) and a significance value of 0.000 which is less than 0.05. Interest influences the decision to purchase Telkomsel cards in the city of Bengkulu, this is evidenced by the tcount value greater than ttable (3.160 > 1.663) and a significance value of 0.002 less than 0.05. Desire influences the decision to purchase Telkomsel cards in the city of Bengkulu, this is evidenced by the tcount value greater than ttable (2.441 > 1.663) and a significance value of 0.017 less than 0.05. Action influences the decision to purchase Telkomsel cards in the city of Bengkulu, this is evidenced by the value of tcount greater than ttable (3.606 > 1.663) and a significance value of 0.001, less than 0.05. This means that if the action is increased then the purchase decision will also increase. Attention, interest, desire and action have a joint effect on the decision to purchase a Telkomsel card in the city of Bengkulu, this is evidenced by the value of Fcount being greater than Ftable (28.691 > 2.33) in line with a significance of 0.000 less than 0.05.